2008
DOI: 10.1186/1471-230x-8-38
|View full text |Cite
|
Sign up to set email alerts
|

Erythromycin lacks colon prokinetic effect in children with functional gastrointestinal disorders: a retrospective study

Abstract: BackgroundMotilin, a peptide hormone has a direct excitatory effect on circular smooth muscle strips derived from the human colon. Reduced plasma motilin concentration has been reported in adults with chronic constipation. Erythromycin, a non-peptide motilin receptor agonist, induces phase 3 of the migrating motor complex (MMC) in the antro-duodenum and also reduces oro-cecal transit time. A pediatric study has reported an improvement in clinical symptoms of constipation following erythromycin administration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…One suggestion is that motilin has been retained during evolution to help promote defecation of the hard faecal pellets, which follow the initial excretion and re-ingestion of partly digested faeces (Costa et al, 1997;Sanger et al, 2009). Such activity contrasts with that in humans where the effects of motilin agonists on lower bowel functions have been found to vary (Jameson et al, 1992;Sharma et al, 1995;Bassotti et al, 1998;Emmanuel et al, 2004;Venkatasubramani et al, 2008).…”
Section: Species and Tissue Distribution Of Motilinmentioning
confidence: 99%
“…One suggestion is that motilin has been retained during evolution to help promote defecation of the hard faecal pellets, which follow the initial excretion and re-ingestion of partly digested faeces (Costa et al, 1997;Sanger et al, 2009). Such activity contrasts with that in humans where the effects of motilin agonists on lower bowel functions have been found to vary (Jameson et al, 1992;Sharma et al, 1995;Bassotti et al, 1998;Emmanuel et al, 2004;Venkatasubramani et al, 2008).…”
Section: Species and Tissue Distribution Of Motilinmentioning
confidence: 99%
“…Most recently, in the first pediatric study on this subject, Venkatasubramani et al [17] showed that 1 mg/kg of IV EL infused during colonic manometry failed to increase the MI 60 minutes after infusion in 10 children with normal colonic manometry; their study was limited by its small number, retrospective nature, and relatively low doses of EL. Similar to Venkatasubramani et al [17], we chose to evaluate colonic motility by full colonic manometry, as we believe this to be the most objective and detailed method of documenting motility. Our study builds on the study by Venkatasubramani et al [17] by its larger number, prospective design, higher dose of EL, and inclusion of patients with both normal and abnormal manometry.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to Venkatasubramani et al [17], we chose to evaluate colonic motility by full colonic manometry, as we believe this to be the most objective and detailed method of documenting motility. Our study builds on the study by Venkatasubramani et al [17] by its larger number, prospective design, higher dose of EL, and inclusion of patients with both normal and abnormal manometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term therapy appears to be safe; however, decreased ef fi cacy is seen after prolonged treatment due to downregulation of motilin receptors. There has been no evidence that erythromycin has any prokinetic effect on the colon as shown by administration of the drug during colonic manometry studies [ 36,37 ] .…”
Section: Motilin Agonists Erythromycinmentioning
confidence: 99%